Towards a collaborative experience to generate knowledge: Use of gamification in robotics for Good Agricultural Practices - Lombardelli, Julieta (2020)
Currently gamification strategies are implemented in the most diverse fields. This paper discusses the design of gamification environment on a collaborative wiki on good agricultural practices. The aim of the project is to present a gamification design is complemented by a robotic interface, aimed at increasing customizing the experience from a cooperative community context. The robot interface also presents the possibility of containing a living organism, linked to the actions of the wiki.